G-Quadruplex Structures Colocalize with Transcription Factories and Nuclear Speckles Surrounded by Acetylated and Dimethylated Histones H3 - Komůrková, Denisa; Svobodová Kovaříková, Alena; Bártová, Eva (International journal of molecular sciences, 2021)
G-quadruplexes (G4s) are four-stranded helical structures that regulate several nuclear processes, including gene expression and telomere maintenance. We observed that G4s are located in GC-rich (euchromatin) regions and outside the fibrillarin-positive compartment of nucleoli. Genomic regions around G4s were preferentially H3K9 acetylated and H3K9 dimethylated, but H3K9me3 rarely decorated G4 structures. We additionally observed the variability in the number of G4s in selected human and mouse cell lines. We found the highest number of G4s in human embryonic stem cells. We observed the highest degree of colocalization between G4s and transcription factories, positive on the phosphorylated form of RNA polymerase II (RNAP II). Similarly, a high colocalization rate was between G4s and nuclear speckles, enriched in pre-mRNA splicing factor SC-35. PML bodies, the replication protein SMD1, and Cajal bodies colocalized with G4s to a lesser extent. Thus, G4 structures seem to appear mainly in nuclear compartments transcribed via RNAP II, and pre-mRNA is spliced via the SC-35 protein. However, α-amanitin, an inhibitor of RNAP II, did not affect colocalization between G4s and transcription factories as well as G4s and SC-35-positive domains. In addition, irradiation by γ-rays did not change a mutual link between G4s and DNA repair proteins (G4s/γH2AX, G4s/53BP1, and G4s/MDC1), accumulated into DNA damage foci. Described characteristics of G4s seem to be the manifestation of pronounced G4s stability that is likely maintained not only via a high-order organization of these structures but also by a specific histone signature, including H3K9me2, responsible for chromatin compaction.
Keywords: Cell Line; buněčné jádro; epigeneze genetická; buněčná inkluze; DNA; Epigenesis, Genetic; Inclusion Bodies; metylace; zastoupení bazí; buněčné jadérko; Chromatin; Mice; epigenetics; Transcription, Genetic; genetická transkripce; transcription factories; histony; Cell Nucleus; Histones; DNA repair; G-kvadruplexy; zvířata; Humans; nuclear bodies; Base Composition; oprava DNA; nuclear speckles; acetylace; myši; buněčné linie; chromatin; Cell Nucleolus; G-Quadruplexes; DNA Repair; Acetylation; Methylation; G-quadruplex structure; lidé; Animals